An exploration of “home” in postcolonial context: a close study of V.S. Naipaul’s a house for Mr. Biswas and Salman Rushdie’s Midnight’s children - Zumara, Zannati (BARC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.